A CRITICAL REVIEW AND EVALUATION OF APPLYING SEMI-VOLATILE ORGANIC COMPOUNDS (SVOCS) AS A GEOCHEMICAL TRACER TO INDICATE TSUNAMI BACKWASH: The Bilateral, Deutsche Forschungsgemeinschaft (DFG) and National Research Council of Thailand (NRCT) Funded Project “Tsunami Deposits in Near-Shore- and Coastal Waters of Thailand (TUNWAT)” - Siwatt Pongpiachan; Klaus Schwarzer (Science of Tsunami Hazards, 2013)
Tsunamis symbolize one of the most harmful natural disasters for low-lying coastal zones and their residents, due to both its destructive power and irregularity. The 2004 Boxing Day tsunami, which attack the Andaman Sea coast of Thailand, resulted 5,395 of deaths and inestimable casualties, interrupted economies and social well-being in numerous coastal villages and caused in extreme alterations of both onshore and offshore coastal morphology. The Great Indian Ocean tsunami also highlighted that there are many missing jigsaw puzzle pieces in scientific knowledge, starting from the generating of tsunamis offshore to the countless influences to the marine ecosystems on the continental shelf, coastal areas and on land and to the economic and social systems consequences. As with all deposits that do not have a direct physical link to their causative sources, marine tsunami deposits must be distinguished from other deposits through regional correlation, dating and criteria for recognition within the deposits themselves. This study aims to provide comprehensive reviews on using Polycyclic Aromatic Hydrocarbons (PAHs) as a chemical proxy to discriminate tsunami relateddeposits from typical marine sediments. The advantages and disadvantages of this chemical tracer will be critically reviewed and further discussed.